2000
DOI: 10.1080/026520400288256
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced process for encapsulating aspirin in ethyl cellulose microcapsules by solvent evaporation in an O/W emulsion

Abstract: An enhanced process for microencapsulating aspirin in ethylcellulose was demonstrated using an oil-in-water emulsification/solvent evaporation technique. Methylene chloride (CH2Cl2) was used as the dispersed medium and water as the dispersing medium. The recovered weight, particle size distribution, aspirin loading efficiency, and the aspirin release rate of microcapsules were analysed. The addition of appropriate amounts of non-solvent (n-heptane) prior to the emulsification increases the recovered weight, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This may be the reason why Vivek et al [42] demonstrated that incorporating different lipids (glyceryl monostearate, glyceryl tristearate, WE85 and PRE) to produce olanzapine-loaded SLNs using a melt emulsification and high-pressure homogenization method did not have a significant effect on the particle size. In fact, particle size in such studies is determined by the production procedure parameters, such as the surfactant concentration, the organic/aqueous phase ratio, the proportion of different organic solvents and the homogenization speed [44,45]. It has been reported that the most effective factor on the particle size is the effect of the organic/aqueous phase ratio for the solvent diffusion and evaporation method [43].…”
Section: Particle Size Of Nanoparticlesmentioning
confidence: 99%
“…This may be the reason why Vivek et al [42] demonstrated that incorporating different lipids (glyceryl monostearate, glyceryl tristearate, WE85 and PRE) to produce olanzapine-loaded SLNs using a melt emulsification and high-pressure homogenization method did not have a significant effect on the particle size. In fact, particle size in such studies is determined by the production procedure parameters, such as the surfactant concentration, the organic/aqueous phase ratio, the proportion of different organic solvents and the homogenization speed [44,45]. It has been reported that the most effective factor on the particle size is the effect of the organic/aqueous phase ratio for the solvent diffusion and evaporation method [43].…”
Section: Particle Size Of Nanoparticlesmentioning
confidence: 99%
“…In the realm of controlled drug delivery, several approaches for generating microparticles may be useful. The solvent evaporation method is one of the most frequent ways for preparing microparticles [1][2][3]. Controlling the microparticle preparation processes is critical for achieving the required mean size, size distribution, and shape of microparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of medications, including tiny molecules, proteins, and nucleic acids, can be encapsulated in microparticles. Simple or multiple emulsion procedures such as oilin-water (O/W) or water-in-oil-in-water (W/O/W) are utilized based on the drug's solubility [3][4][5][6]. In the encapsulation and release of pharmaceuticals, the process of microparticle production is a determinant.…”
Section: Introductionmentioning
confidence: 99%
“…The herbicide norflurazon was encapsulated in ethylcellulose (EC40) microspheres by the solvent evaporation technique to obtain controlled release formulations, which show large encapsulation efficiency for the herbicide [65]. Aspirin were encapsulated with ethylcellulose by oil-in-water emulsification/solvent evaporation technique, The release rate follows first-order kinetics during the first 12 hours, suggesting a monolithic system with aspirin uniformly distributed in the microcapsule [66]. Solvent evaporation method was used to prepare ibuprofen encapsulated ethylcellulose which evidenced the presence of a metastable molecular dispersion for intermediate loadings, coexisting with a solid solution and a crystalline dispersion of the drug in the polymer matrix [67].…”
Section: Encapsulation Using Ethylcellulose As Core Shellmentioning
confidence: 99%